2020
DOI: 10.1128/msphere.00914-19
|View full text |Cite
|
Sign up to set email alerts
|

Acute Sleep-Wake Cycle Shift Results in Community Alteration of Human Gut Microbiome

Abstract: Disturbances of sleep and the underlying circadian rhythm are related to many human diseases, such as obesity, diabetes, cardiovascular disorders, and cognitive impairments. Dysbiosis of the gut microbiome has also been reported to be associated with the pathologies of these diseases. Therefore, we proposed that disturbed sleep may regulate gut microbiota homeostasis. In this study, we mimicked the sleep-wake cycle shift, one typical type of circadian rhythm disturbances in young people, in recruited subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 46 publications
2
31
1
1
Order By: Relevance
“…For example, a study of 10 male security guards who worked both Full-size DOI: 10.7717/peerj.11406/fig- 5 day and night shifts found there were no significant differences in in alpha or beta diversity within and across-subject variation for both shifts (Mortas, Bilici & Karakan, 2020). In contrast, slight changes in microbial abundance and diversity were noted when 22 subjects, aged 20-35 years, delayed their sleep period for 2-4 h (Liu et al, 2020). Although there have been studies comparing circadian variation in the gut microbiota in mice (Thaiss et al, 2014) and another describing the results samples collected during multiple time points over several days by two subjects (Thaiss et al, 2014), our study is the first to compare the richness and diversity of gut microbiota collected from 51 human participants at two different time points in 24 h. Even though there are numerous studies that have reported increased and/or decreased amounts of various gut bacteria among patients with IBS (Bhattarai, Pedrogo & Kashyap, 2017;Casén et al, 2015;Pittayanon et al, 2019;Salonen, de Vos & Palva, 2010;Tap et al, 2017), a recent systematic review found only nine studies that discussed differences in alpha-diversity in patients with IBS compared to normal controls (Pittayanon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study of 10 male security guards who worked both Full-size DOI: 10.7717/peerj.11406/fig- 5 day and night shifts found there were no significant differences in in alpha or beta diversity within and across-subject variation for both shifts (Mortas, Bilici & Karakan, 2020). In contrast, slight changes in microbial abundance and diversity were noted when 22 subjects, aged 20-35 years, delayed their sleep period for 2-4 h (Liu et al, 2020). Although there have been studies comparing circadian variation in the gut microbiota in mice (Thaiss et al, 2014) and another describing the results samples collected during multiple time points over several days by two subjects (Thaiss et al, 2014), our study is the first to compare the richness and diversity of gut microbiota collected from 51 human participants at two different time points in 24 h. Even though there are numerous studies that have reported increased and/or decreased amounts of various gut bacteria among patients with IBS (Bhattarai, Pedrogo & Kashyap, 2017;Casén et al, 2015;Pittayanon et al, 2019;Salonen, de Vos & Palva, 2010;Tap et al, 2017), a recent systematic review found only nine studies that discussed differences in alpha-diversity in patients with IBS compared to normal controls (Pittayanon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of 10 male security guards who worked both day and night shifts found there were no significant differences in in alpha or beta diversity within and across-subject variation for both shifts ( Mortas, Bilici & Karakan, 2020 ). In contrast, slight changes in microbial abundance and diversity were noted when 22 subjects, aged 20–35 years, delayed their sleep period for 2–4 h ( Liu et al, 2020 ). Although there have been studies comparing circadian variation in the gut microbiota in mice ( Thaiss et al, 2014 ) and another describing the results samples collected during multiple time points over several days by two subjects ( Thaiss et al, 2014 ), our study is the first to compare the richness and diversity of gut microbiota collected from 51 human participants at two different time points in 24 h.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between circadian rhythms and diverse gut microbiota has been well studied, where the acute sleep-wake cycle shift alters the functional profiles of gut microbes. Together, the clock-microbial communities affect host homeostasis [ 58 ]. The circadian rhythm of SCFA production was observed by Segers et al to cause rhythmicity in intestinal movement [ 59 ].…”
Section: Mechanisms Underlying the Interaction Between Gut Microbimentioning
confidence: 99%
“…Shift work promotes unhealthy snacking behaviour, as well as abnormal glucose tolerance, 182‐186 thereby increasing the risk for obesity and type 2 diabetes. In addition, circadian disruption because of genetic perturbation or misalignment of endogenous and exogenous rhythms has been found to cause dysbiosis of the gut microbiome 187‐190 . Vice versa, changes to the microbiome, for example by antibiotics, altered diet, age or stress, may disrupt endogenous clock functions of the gastrointestinal tract and promote metabolic disease 191 .…”
Section: Modern Life Challenges To the Human Circadian Systemmentioning
confidence: 99%